Audio Visual Literacy Media Based on Fable Story to Increase Student Reading Interest for Second Grade of Elementary Student - Darmayanti, Ni Nyoman Karina Mas; Suarni, Ni Ketut; Wibawa, I Made Citra (Journal of Education Technology, 2024)
This paper was carried out based on the lack of variety in literacy media that the teachers provide, especially in literacy activities before the learning section started. This causes students tend to have lack of enthusiasm or interest in reading when the school literacy movement begins. This paper aims to develop audio-visual literacy media based on fable stories for the student in grade II class of elementary school. This paper uses the ADDIE (Analyse, Design, Development, Implementation, and Evaluation) development model. The subjects in this research were 2 content experts, 2 learning media experts, 2 learning video design experts, 2 practitioners, 3 individual trial students, and 9 small group trial students. Meanwhile, the object of this paper is audio-visual literacy media. The methods used are interviews, observation, questionnaires, and tests. Based on the results of the validity, practicality, and effectiveness tests carried out, overall, it has a very good category. Meanwhile, the results of the effectiveness test calculations carried out obtained a t count of 1.819 while the table was 1.745, so it can be concluded that Indonesian language learning outcomes before using audio-visual literacy media based on fable stories. The implication of this research is that audio-visual literacy media based on fable stories in class II elementary school with qualifications is very helpful in supporting the learning process in the classroom. Thus, the research results show that audio-visual literacy media based on fable stories are feasible and effective for use in the literacy activity process.